The DIC carbon isotope evolutions during CO2 bubbling: Implications for ocean acidification laboratory culture - Zhang, Hongrui; Torres-Romero, Ismael; Anjewierden, Pien; Jaggi, Madalina; Stoll, Heather M. (Frontiers in Marine Science, 2022)
Ocean acidification increases pCO2 and decreases pH of seawater and its impact on marine organisms has emerged as a key research focus. In addition to directly measured variables such as growth or calcification rate, stable isotopic tracers such as carbon isotopes have also been used to more completely understand the physiological processes contributing to the response of organisms to ocean acidification. To simulate ocean acidification in laboratory cultures, direct bubbling of seawater with CO2 has been a preferred method because it adjusts pCO2 and pH without altering total alkalinity. Unfortunately, the carbon isotope equilibrium between seawater and CO2 gas has been largely ignored so far. Frequently, the dissolved inorganic carbon (DIC) in the initial seawater culture has a distinct 13C/12C ratio which is far from the equilibrium expected with the isotopic composition of the bubbled CO2. To evaluate the consequences of this type of experiment for isotopic work, we measured the carbon isotope evolutions in two chemostats during CO2 bubbling and composed a numerical model to simulate this process. The isotopic model can predict well the carbon isotope ratio of dissolved inorganic carbon evolutions during bubbling. With help of this model, the carbon isotope evolution during a batch and continuous culture can be traced dynamically improving the accuracy of fractionation results from laboratory culture. Our simulations show that, if not properly accounted for in experimental or sampling design, many typical culture configurations involving CO2 bubbling can lead to large errors in estimated carbon isotope fractionation between seawater and biomass or biominerals, consequently affecting interpretations and hampering comparisons among different experiments. Therefore, we describe the best practices on future studies working with isotope fingerprinting in the ocean acidification background.